Gestational diabetes and cardiovascular risk factors and disease in U.S. Hispanics/Latinas in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Issue 5 (28th May 2019) - Perera, Marisa J; Reina, Samantha A; Elfassy, Tali; Potter, JoNell E; Sotres Alvarez, Daniela; Simon, Melissa A.; Isasi, Carmen R.; Stuebe, Alison M.; Schneiderman, Neil; Llabre, Maria M.
ABSTRACT: To compare cardiovascular risk and disease prevalence in U.S. Hispanics/Latinas with and without a history of gestational diabetes mellitus (GDM). Cross-sectional data from 2008 to 2011 were analyzed for 8, 262 (305 with GDM history) parous women, aged 20–73 years, from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Women with and without a history of GDM were compared on sociodemographic, cardiovascular risk factor, and disease data from standardized interviews and fasting blood tests, using chi-square tests, t -tests, and logistic regressions to determine odds ratios (ORs) and 95 percent confidence intervals (CIs). Adjusting for covariates, compared to those without a history of GDM, women with a history of GDM were younger ( M  = 39.1 years [95 percent CI = 37.8, 41.6] vs. 45.5 years [95 percent CI = 44.9, 46.1]) and more likely to have health insurance (68.1 percent [95 percent CI = 60.3 percent, 76.0 percent] vs. 54.9 percent [95 percent CI = 52.8 percent, 57.1 percent]), had greater waist circumference ( M  = 102.3 cm, [95 percent CI = 100.2, 104.3] vs. 98.1 cm [95 percent CI = 97.4, 98.5]) and higher fasting glucose (116.0 mg/dL [95 percent CI = 107.8, 124.3] vs. 104.2 mg/dL [95 percent CI = 103.4, 105.1]), and had higher odds of having metabolic syndrome (OR = 1.7 [95 percent CI = 1.2, 2.6]) or diabetes (OR = 3.3 [95 percent CI = 2.2, 4.8]). Prevalences of heart and cerebrovascular disease were similar. GDM history was positively associated with diabetes but not with cardiovascular disease.